Developing ABCS Learning Media for Physical Fitness Activities of Junior High School Students - Ananda Pramudya Wardhana; Agus Darmawan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The lack of varied instructional media in Physical Education (PJOK) causes low student motivation and movement participation. This study aims to develop and test the feasibility and effectiveness of the ABCS (Agility, Balance, Coordination, Strength) learning media innovation. The approach used is Research and Development (R&D) adopting Sugiyono's methodology. Data evaluation involved feasibility validation by three experts (material, media, practitioner) and field trials on a small scale (67 students) and a large scale (173 students) using questionnaires. The results showed that expert validation reached an average of 93.33% (Very Feasible). During field trials, implementation effectiveness increased significantly from 84.29% (small scale) to 91.53% (large scale), with the highest surge in the affective aspect (91.94%). The use of four-color stimuli and integrated barcode tutorials successfully broke the monotony and boosted students' enthusiasm. In conclusion, the ABCS media is highly feasible, practical, and effective as a pedagogical solution to optimize physical fitness learning.